PARTISIPASI MASYARAKAT PERBATASAN DALAM PEMBANGUNAN POS LINTAS BATAS NEGARA (PLBN) JAGOI BABANG - Abao, Antonia Sasap; Gaffar, Zakiah Hasan (Social Welfare Study Program, 2022)
Abstract. This paper discusses the response and readiness of the community to the development of the Jagoi Babang PLBN and analyzes the forms of participation of the Jagoi Babang border community in the stages of the development process and utilization of the Jagoi Babang PLBN. Data and information in this study were collected using in-depth interviews, Focus Group Discussions and non-participant observation. Furthermore, the data was processed in a qualitative descriptive method. The results showed that the Jagoi Babang border community generally responded positively to the development of the PLBN because it was felt very helpful for them in carrying out cross-border activities safely and comfortably. The community also hopes that developing the PLBN will help the community improve the economic level and open up new job opportunities, especially for local youth who have successfully received higher education outside Jagoi-Babang. Another important finding is that the Jagoi Babang border community has participated and is currently participating in the planning process and the implementation phase of the physical development of the PLBN in a very limited scope. Workers outside the Jagoi area still dominate most construction work. Community involvement is still focused on the low-skill work sector as manual labour, such as stone transporters, cement casters, construction workers, cleaners/ sweepers and security guards. Furthermore, in the plan to utilize the PLBN, the Immigration and Customs Office will actively involve residents as workers, either as administrative employees or as unskilled labourers or other non-skilled workers. In addition, residents will also be provided with facilities for trading by utilizing market buildings/shops/kiosks built around the PLBN to sell various garden/agricultural products and handicrafts. Keywords: Participation; Society; Border; PLBN; Jagoi Babang Abstrak. Kertas kerja ini membahas tentang tanggapan dan kesiapan masyarakat terhadap pembangunan PLBN serta menganalisis bentuk-bentuk partisipasi masyarakat perbatasan Jagoi Babang dalam tahapan proses pembangunan dan pemanfaatan PLBN Jagoi Babang. Data dan informasi dalam penelitian ini dikumpulkan dengan metode wawancara mendalam, Focus Group Discussion dan observasi non-partisipan. Selanjutnya data diolah secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa pada umumnya masyarakat perbatasan Jagoi Babang merespon positif pembangunan PLBN karea dirasakan sangat membantu masyarakat perbatasan dalam melakukan kegiatan lintas batas negara dengan aman dan nyaman. Masyarakat juga berharap agar pembangunan PLBN bukan hanya dapat membantu masyarakat memperbaiki tingkat perekonomian, namun juga membuka lapangan pekerjaan baru, khususnya bagi para pemuda setempat yang telah berhasil mengenyam pendidikan tinggi di luar Jagoi-Babang. Temuan penting lainnya yaitu masyarakat perbatasan Jagoi Babang telah dan sedang berpartisipasi dalam proses perencanaan dan tahap pelaksanaan pembangunan fisik PLBN di lingkup yang sangat terbatas. Sebagian besar pekerjaan pembangunan, masih didominasi oleh tenaga kerja dari luar daerah Jagoi. Ranah keterlibatan masyarakat masih terfokus pada sektor pekerjaan yang rendah skill sebagai pekerja kasar seperti pengangkut batu, pengecor semen, tukang bangunan, tukang bersih/ tukang sapu dan satpam (security). Selanjutnya dalam rencana pemanfaatan PLBN, pihak Imigrasi dan Bea Cukai akan mengikutsertakan penduduk lokal secara aktif sebagai tenaga kerja baik sebagai pegawai administrasi mau pun sebagai buruh kasar atau pekerja non-skilled lainnya. Selain itu, penduduk setempat juga akan disediakan fasilitas untuk berdagang dengan memanfaatkan bangunan pasar/ruko/kios yang di bangun di sekitar PLBN untuk berjualan berbagai hasil kebun/pertanian dan hasil karya kerajinan. Kata kunci: Partisipasi; Masyarakat, perbatasan; PLBN; Jagoi Babang